« Ce que nous voulons, c’est une Commission vérité et réconciliation ». La justice transitionnelle en Mauritanie : un modèle, sa promotion et des évitements politiques - Sidi N’Diaye (L’Année du Maghreb)
In 2007, when Sidi Ould Cheikh Abdellahi came to power, he launched a process of “national reconciliation” which was intended to bring about public recognition of the violence from the 1980s and 1990s and its victims. But very quickly, the measures in favor of that policy of recognition and the possibility of seeing the whole truth emerge, deplored the army Generals, on top of the former regime. They seized power in August 2008. With the General Ould Abdel Aziz who took over from Ould Cheikh Abdellahi, the process of national reconciliation brought about confusion and ambiguity. The work of military authorities, in collaboration with a group of victims, seemed to many others to be an attempt to remove the painful past. It was therefore urgent, according to the “excluded” victims, to return to the negotiation table. Facing the unwillingness of the authorities to return to the negotiations, some victims’ groups and human rights organizations, along with international NGOs, tackled the issue over the violence from the past and its consequences by resorting to a mechanism to end the crisis, which was the subject of promising discussions during the short mandate of Ould Cheikh Abdellahi: transitional justice. Based on interviews with victims involved in associative and political bodies, on public statements from associative leaders and the work of victims’ associations and of international NGOs, this article reports on the conditions to introduce transitional justice into the debate on “national reconciliation”, but also on the work of promoting this model by associative actors and their international partners. In addition, as this promotional effort has met with the reluctance of the official authorities, the article looks back at the motivations of the latter, before concluding wih the ongoing demands of victim’s organizations.